Key Criteria in the Choice of IoT Platforms in Spanish Companies - Alfonso Infante-Moro (MDPI AG, 2021)
The level of implementation of IoT technology in Spanish companies is not low for a novel technology, but there are concerns that hinder its level of implementation from being higher: initial costs, security, and privacy. These concerns could be solved with the choice of the appropriate IoT platform, but it must be taken into account that there are numerous criteria that participate in this decision that influence each other. This could give rise to criteria not being considered at first, even though they should be taken into account in this choice. Existing studies do not consider this. Thus, the objective of this study was to find out what are the key criteria to be taken into account by Spanish companies when choosing an IoT platform. The criteria were located through a literary review, and classified according to their level of importance in this decision through a causal study carried out with the methodology of fuzzy cognitive maps. The results achieved showed that there were key criteria beyond the criteria directly implied by the concerns, such as stability, scalability, flexibility, and interoperability, and these new criteria acquired the same or greater importance.